Effect of Hydrological Properties on the Energy Shares of Reflected Waves at the Surface of a Partially Saturated Porous Solid - Mahabir Barak; Manjeet Kumari; Manjeet Kumar (AIMS Geosciences, 2017)
In the present study, the reflection of inhomogeneous waves is investigated at the stress-free plane surface based on multiphase poroelasticity theory. The porous medium is considered as dissipative due to the presence of viscosity in pores fluid. Four inhomogeneous (i.e. different direction of propagation and attenuation) reflected waves (three longitudinal and one shear) exists due to an incident wave. By using the appropriate boundary conditions, closed-form analytical expressions for the reflection coeffcients are derived at the stress-free surface. These reflection coeffcients are used to drive the analytical expressions for the energy shares of various reflected inhomogeneous waves. In mathematical framework, the conservation of incident energy is confirmed by considering an interaction energy between two dissimilar waves. It validates that the numerical calculations are analytically correct. Finally, a numerical example is considered to study the effects of viscous cross-coupling, porosity, saturation of gas, pore-characteristics and wave frequency on the energy shares of various reflected inhomogeneous waves and depicted graphically.